Burden of Candidemia in the United States, 2017. (28th February 2020) - Tsay, Sharon V; Mu, Yi; Williams, Sabrina; Epson, Erin; Nadle, Joelle; Bamberg, Wendy M; Barter, Devra M; Johnston, Helen L; Farley, Monica M; Harb, Sasha; Thomas, Stepy; Bonner, Lindsay A; et al.
Abstract: Background: Candidemia is a common healthcare-associated bloodstream infection with high morbidity and mortality. There are no current estimates of candidemia burden in the United States (US). Methods: In 2017, the Centers for Disease Control and Prevention conducted active population-based surveillance for candidemia through the Emerging Infections Program in 45 counties in 9 states encompassing approximately 17 million persons (5% of the national population). Laboratories serving the catchment area population reported all blood cultures with Candida, and a standard case definition was applied to identify cases that occurred in surveillance area residents. Burden of cases and mortality were estimated by extrapolating surveillance area cases to national numbers using 2017 national census data. Results: We identified 1226 candidemia cases across 9 surveillance sites in 2017. Based on this, we estimated that 22 660 (95% confidence interval [CI], 20 210–25 110) cases of candidemia occurred in the US in 2017. Overall estimated incidence was 7.0 cases per 100 000 persons, with highest rates in adults aged ≥ 65 years (20.1/100 000), males (7.9/100 000), and those of black race (12.3/100 000). An estimated 3380 (95% CI, 1318–5442) deaths occurred within 7 days of a positive Candida blood culture, and 5628 (95% CI, 2465–8791) deaths occurred during the hospitalization with candidemia. Conclusions: Our analysis highlights the substantial burden of candidemia in the US. Because candidemia is only one form of invasive candidiasis, the true burden of invasive infections due to Candida is higher. Ongoing surveillance can support future burden estimates and help assess the impact of prevention interventions. Abstract : Using population-based surveillance that includes 5% of the US population, we estimated that the incidence of candidemia nationally was 7 cases per 100 000 persons and that there were nearly 23 000 cases of candidemia and 3400 deaths in 2017.